2014
DOI: 10.1177/1362361314557548
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a fundamental motor skill intervention for 4-year-old children with autism spectrum disorder: A pilot study

Abstract: A wait-list control experimental design was employed to investigate the effectiveness of a fundamental motor skill intervention at improving the motor skills, adaptive behavior, and social skills of 4-year-old children with autism spectrum disorder (experimental n = 5, control n = 4); the impact of intervention intensity was also explored. The experimental group significantly improved their object manipulation and overall motor scores from pre- to post-intervention. The wait-list control design revealed no gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 36 publications
1
77
1
5
Order By: Relevance
“…Following a 12-week intervention, the experimental group achieved significant gains in gross motor skills (PDMS-2) (Bremer et al, 2014). While significant changes were not reported in either social skills or adaptive behavior, there is evidence to support that proficiency in motor skills at 2 years of age is a significant predictor of optimal outcomes at 4 years of age in children with ASD (Sutera et al, 2007).…”
mentioning
confidence: 96%
“…Following a 12-week intervention, the experimental group achieved significant gains in gross motor skills (PDMS-2) (Bremer et al, 2014). While significant changes were not reported in either social skills or adaptive behavior, there is evidence to support that proficiency in motor skills at 2 years of age is a significant predictor of optimal outcomes at 4 years of age in children with ASD (Sutera et al, 2007).…”
mentioning
confidence: 96%
“…However, this seemingly is a common issue when considering research on children with ASD (see Bremer et al, 2014;Staples and Reid, 2010). Further, due to the small number of individuals and the heterogeneity associated with ASD, the generalizability of the findings of this study are limited.…”
Section: Limitationsmentioning
confidence: 88%
“…Two of the more recent studies Bremer, Balogh, & Lloyd, 2014) demonstrate an increasing awareness of the needs of children with ASD in relation to motor development. For example, Bremer and colleagues (2014), in a small sample (n = 9) pilot study of 4-yearold children with ASD, demonstrated an FMS intervention's positive effect on gross motor skills, as well as improvements in adaptive behavior and social skills.…”
Section: Lack Of Motor Intervention For Asdmentioning
confidence: 99%
See 2 more Smart Citations